We will learn how to express the multiple angle of sin 3A in terms of A or sin 3A in terms of sin A.
Trigonometric function of sin 3A in terms of sin A is also known as one of the double angle formula.
If A is a number or angle then we have, sin 3A = 3 sin A - 4 sin^3 A.
Now we will proof the above multiple angle formula step-by-step.
Proof: sin 3A
= sin (2A + A)
= sin 2A cos A + cos 2A sin A
= 2 sin A cos A ∙ cos A + (1 - 2 sin^2 A) sin A
= 2 sin A (1 - sin^2 A) + sin A - 2 sin^3 A
= 2 sin A - 2 sin^3 A + sin A - 2 sin^3 A
= 3 sin A - 4 sin^3 A
Therefore, sin 3A = 3 sin A - 4 sin^3 A Proved
Note: (i) In the above formula we should note that the angle on the R.H.S. of the formula is one-third of the angle on L.H.S. Therefore, sin 60° = 3 sin 20° - 4 sin^3 20°.
(ii) To find the formula of sin 3A in terms of sin A we have used cos 2A = 1 - 2 sin^2 A
Now, we will apply the formula of multiple angle of sin 3A in terms of A or sin 3A in terms of sin A to solve the below problems.
1. Prove that sin A ∙ sin (60 - A) sin (60 + A) = ¼ sin 3A.
Solution:
L.H.S. = sin A ∙ sin (60° - A) sin (60° + A)
= sin A (sin^2 60° - sin^2 A), [Since, sin (A + B) sin (A - B) = sin^2 A - sin^2 B]
= sin A [(√3/2)^2 - sin^2 A), [Since we know that sin 60° = ½]
= sin A (3/4 - sin^2 A)
= ¼ sin A (3 - 4 sin^2 A)
= ¼ (3 sin A - 4 sin^3 A)
Now apply the formula of sin 3A in terms of A
= ¼ sin 3A = R.H.S. Proved
2. If cos θ = 12/13 find the value of sin 3θ.
Solution:
Given, cos A = 12/13
We know that sin^2 A + cos^2 A = 1
⇒ sin^2 A = 1 - cos^2A
⇒ sin A = √(1 - cos^2A)
Therefore, sin A = √[1 - (12/13)^2]
⇒ sin A = √[1 - 144/169]
⇒ sin A = √(25/169)
⇒ sin A = 5/13
Now, sin 3A = 3 sin A - 4 sin^3 A
= 3 ∙ 5/13 - 4 ∙ (5/13)^3
= 15/13 - 500/2199
= (2535 - 500)/2199
= 2035/2199
3. Show that, sin^3 A + sin^3 (120° + A) + sin^3 (240° + A) = - ¾ sin 3A.
Solution:
L.H.S = sin^3 A + sin^3 (120° + A) + sin^3 (240° + A)
= ¼ [4 sin^3 A + 4 sin^3 (120° + A) + 4 sin^3 (240° + A)]
= ¼ [3 sin A - sin 3A + 3 sin (120° + A) - sin 3 (120° + A) + 3 sin (240° + A) - sin 3 (240° + A)]
[Since we know that, sin 3A = 3 sin 3A - 4 sin^3 A
⇒ 4 sin^3 A = 3 sin A − sin 3A]
= ¼ [3 {sin A + sin (120° + A) + sin (240° + A)} - {sin 3A + sin (360° + 3A) + sin (720° + 3A)}]
= 1/4 [3 {sin A + 2 sin (180° + A) cos 60°) - (sin 3A + sin 3A + sin 3A)}
= ¼ [3 {sin A + 2 ∙ (- sin A) ∙ 1/2} - 3 sin A]
= ¼ [3 {sin A - sin A} - 3 sin A]
= - ¾ sin 3A = R.H.S. Proved
11 and 12 Grade Math
From sin 3A in Terms of A to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Sep 14, 24 04:31 PM
Sep 14, 24 03:39 PM
Sep 14, 24 02:12 PM
Sep 13, 24 02:48 AM
Sep 12, 24 03:07 PM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.